Heat effects on drug delivery across human skin. (3rd May 2016) - Hao, Jinsong; Ghosh, Priyanka; Li, S. Kevin; Newman, Bryan; Kasting, Gerald B.; Raney, Sam G.
ABSTRACT: Introduction : Exposure to heat can impact the clinical efficacy and/or safety of transdermal and topical drug products. Understanding these heat effects and designing meaningful in vitro and in vivo methods to study them are of significant value to the development and evaluation of drug products dosed to the skin. Areas covered : This review provides an overview of the underlying mechanisms and the observed effects of heat on the skin and on transdermal/topical drug delivery, thermoregulation and heat tolerability. The designs of several in vitro and in vivo heat effect studies and their results are reviewed. Expert opinion : There is substantial evidence that elevated temperature can increase transdermal/topical drug delivery. However, in vitro and in vivo methods reported in the literature to study heat effects of transdermal/topical drug products have utilized inconsistent study conditions, and in vitro models require better characterization. Appropriate study designs and controls remain to be identified, and further research is warranted to evaluate in vitro-in vivo correlations and the ability of in vitro models to predict in vivo effects. The physicochemical and pharmacological properties of the drug(s) and the drug product, as well as dermal clearance and heat gradients may require careful consideration.